Binaural perception of amplitude and frequency modulated signals - OZIMEK, E.; WICHER, A. (Archives of Acoustics, 2000)
The investigations focused on the binaural perception of amplitude modulated (AM) and frequency modulated (FM) signals. They are comprised of two experiments. In the first experiment binaurally perceived (matched) modulation depth for AM signals was determined under diotic conditions (i.e. for the same values of modulation depth coefficient, m, presented to the left (ml) and right (mr) ears) and under dichotic conditions (i.e. for different values of these coefficients ml 6 = mr). The measurements were made for the interaural differences in modulation depth coefficient Δm, changing from 0 to 100% and a few selected modulating frequencies (4, 64 and 128 Hz) and carrier frequencies (250 and 1000 Hz). In the second experiment binaurally perceived (matched) frequency deviation of FM signals was determined under diotic conditions (i.e. for the same values of frequency deviation, Δf, presented to the left (Δfl) and right (Δf